Energy Efficiency Measures in Public Sector: An Empirical Analysis of the Determinants of Adoption of Low-Cost Energy Efficiency - Mulyaningsih, Mulyaningsih; Setiadi, Ade; Setiawan, Iwan; Susniwati, Susniwati; Erna, Erna; Fauzi, Teddy Hikmat (International Journal of Energy Economics and Policy, 2024)
This research delves into the intricate interplay between leadership styles, eco-innovation, and energy efficiency in the Indonesian public sector, examining the roles of green transformational leadership and ethical leadership. Acknowledging the pivotal role of public sector institutions in fostering sustainable practices, the study addresses the ongoing debate surrounding the efficacy of these leadership styles in the context of eco-innovation and energy efficiency. Using a quantitative research approach, data was collected from 227 faculty members across various Indonesian public sector institutions through a questionnaire. SmartPLS 4 software was employed for data analysis. The findings reveal that green transformational leadership positively influences eco-innovation, yet it does not directly impact energy efficiency. Conversely, ethical leadership does not directly drive eco-innovation but demonstrates a positive association with energy efficiency. Eco-innovation emerges as a direct contributor to energy efficiency. Significantly, the research identifies eco-innovation as a mediator between green transformational leadership and energy efficiency. However, this mediating effect is not observed in the relationship between ethical leadership and energy efficiency. The study underscores the need for leadership emphasizing environmental consciousness and ethics, coupled with the promotion of eco-innovation, to effectively attain sustainability and energy efficiency objectives within the Indonesian public sector.